Occupational demands, psychological burnout and anxiety among hospital personnel in norway - AM Richardsen; RJ Burke; MP Leiter (1992)
The present study reports the results of a questionnaire survey among 212 health care workers at a hospital in Northern Norway. Measures included burnout, trait anxiety, various job demands and supports, and work attitudes (job satisfaction and organizational commitment). Results provided support for Maslach's conceptualization of the burnout syndrome cross-culturally. Correlations among the three burnout subscales, as well as organizational correlates of burnout were generally consistent with earlier findings. The burnout scores of hospital workers were higher than North American norms, and some occupational differencs among subscales were found. A model of individual characteristics, job demands, burnout, and work attitudes was tested through a series of multiple regressions. Trait anxiety as well as job demands contributed to burnout. The influence of trait anxiety on work attitudes was mediated through emotional exhaustion. However, in addition to emotional exhaustion, both job demands and organizational supports had direct effects on work attitudes. Thus, burnout does not fully operate as a mediating variable between demands and attitudes such as commitment. The study also addressed the issue of individual differences in the burnout response and focused on the need to systematically investigate the relaive importance of situational versus personality variables in future burnout research. © 1992, Taylor & Francis Group, LLC. All rights reserved.